Luke Cage as Postpost-9/11 TV: Spatial Negotiations of Race in Contemporary U.S. Television - Lea Espinoza Garrido (Current Objectives of Postgraduate American Studies)
Reading Luke Cage “as a ‘postpost-9/11’ text with a focus on the body of the bulletproof Black male superhero, Luke, as well as the show’s setting, this paper examines the serial’s potential to negotiate social and cultural implications of American politics in response to the attacks on September 11, 2001, particularly with regard to the War on Terror’s embeddedness in long-standing histories of racism.